Pengaruh Fermentasi dan Asal Biji Kakao Terhadap Mutu Produk Olahan Kakao (Coklat Batang) - Darmawan, D; Yusuf, Muhammad; Wisdawati, Eka; Poleuleng, Andi Besse; Monika, M; Ayu, Andi; Hala, Dian; Slamet, S; Zulkifli, Z; Wardani, Firda (Journal Galung Tropika, 2023)
The source of raw materials and the fermentation process carried out really need to be considered when processing it into chocolate bar products. This research aimed to determine the effect of seed origin and fermentation treatment on product quality and quality. The treatments in this research were cocoa beans from Soppeng Regency (South Sulawesi) and Polman Regency (West Sulawesi) with differences in fermentation time, namely 5 days and 7 days. The research results show that the raw material for cocoa beans used in making processed chocolate bars is influenced by the origin of the beans and the fermentation treatment. Visual test results showed that there was no difference in results for seeds from Soppeng and Polman. The processed product is brown in color and has a distinctive aroma because it comes from fermented cocoa beans. Testing for water content and fat content is greatly influenced by the fermentation process where a good stirring process during the fermentation process can increase the fat content and reduce the water content. Test results for metal contamination: Lead <0.0134, Cadmium <0.0013, Tin <0.0776, Mercury and Arsenic <0.0002. The results of microbial testing were TPC 1.2 x 101 and 7.0 x 101 colonies/g, Escherichia coli <3, Mold and Yeast 1.3 x 102 and 7.0 x 101 colonies/g and Salmonella was negative. The results of testing for metal contamination and microbiology show that processed cocoa products (chocolate bars) at the Politani Pangkep cocoa processing workshop are safe for consumption because they have test results below the SNI reference value.